4u-46=-2(u+8)

Simple and best practice solution for 4u-46=-2(u+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4u-46=-2(u+8) equation:



4u-46=-2(u+8)
We move all terms to the left:
4u-46-(-2(u+8))=0
We calculate terms in parentheses: -(-2(u+8)), so:
-2(u+8)
We multiply parentheses
-2u-16
Back to the equation:
-(-2u-16)
We get rid of parentheses
4u+2u+16-46=0
We add all the numbers together, and all the variables
6u-30=0
We move all terms containing u to the left, all other terms to the right
6u=30
u=30/6
u=5

See similar equations:

| 6x-12=3x+4-× | | Z+20=y | | 3m^2-11m=9=0 | | X2-30=7x | | 1/3x=2=7x | | 4x+15=6x-11=180 | | 3/7-x=5/4 | | 10=y/5-15 | | −6x+85=61 | | 14(2x-1)+11=1111 | | 2z/9+7=-6 | | x-10=15/2 | | -2=(-7y+1)+5(8+2y) | | 4y+16=96 | | 24x-4=0 | | 10x-1=-5x+29 | | Y=2x+3/2 | | 16x+12=44 | | 3r+2=2 | | z/9+9=5 | | Y/2y-9=3+8y | | 19{9-3x}+2x=516 | | 5x+4/3=x+9/2 | | y-7/2=5 | | 5y+2+80=180 | | 17.15x-15x=7x-13 | | -9x+50=-13 | | 4x+32=24+3x | | Y=7.2x-5 | | 4q^2+q-2=0 | | 12q^2-11q+2=0 | | a-1×1÷2=1÷2 |

Equations solver categories